A Study on The Removal of Some Environmentally Polluting Textile Dyes Using Thiazole Complexes - Falih Jabr, Zainab Hussein; Hashem, Bushra Ali Saleh; Ahmed, Amina Said Hameed; Abdalkareem Abdalmuhsen, Samerah Abd Alrauf; Abbas, Zaman Haqi Ismail (American Journal of Biodiversity, 2024)
Study of textile dyes which are chemical substances and compounds used for the purpose of producing and preparing materials that last for a long period. We have previously indicated that in order for a substance to act as a dye, it must be able to fix itself and have the ability to fix on the fabric. There are no chromogens that act as dyes because the presence of a salt-forming group is necessary. Auxochromes and similar groups, regardless of their specialization (as auxochromes) in order to make the color deep, their presence is necessary to make the chromogen a dye. Thus, auxochromes perform two functions.